2012
DOI: 10.1186/1477-7517-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing cannabis for harm reduction

Abstract: Neuropathic pain affects between 5% and 10% of the US population and can be refractory to treatment. Opioids may be recommended as a second-line pharmacotherapy but have risks including overdose and death. Cannabis has been shown to be effective for treating nerve pain without the risk of fatal poisoning. The author suggests that physicians who treat neuropathic pain with opioids should evaluate their patients for a trial of cannabis and prescribe it when appropriate prior to using opioids. This harm reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 48 publications
1
58
0
1
Order By: Relevance
“…Physicians in primary care, pain management, hospital emergency departments, and other clinical settings can deliver overdose prevention training and prescribe naloxone to patients at risk of opioid overdose (Beletsky et al, 2007; Burris et al, 2001; Mayet et al, 2011) though the practice is relatively uncommon, particularly among those who are not familiar or comfortable with the health concerns of people who use drugs (Beletsky et al, 2007). The criminal justice system is another venue where drug users at high risk for opioid overdose could be targeted for OEND interventions, in light of calls for the criminal justice system to align with public health goals (Silverman et al, 2012) and increased attention to the role that law enforcement officers can play in responding to the epidemic of opioid overdose death (Banta-Green et al, 2013; Davis et al, 2014; Green et al, 2013b; Ray et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Physicians in primary care, pain management, hospital emergency departments, and other clinical settings can deliver overdose prevention training and prescribe naloxone to patients at risk of opioid overdose (Beletsky et al, 2007; Burris et al, 2001; Mayet et al, 2011) though the practice is relatively uncommon, particularly among those who are not familiar or comfortable with the health concerns of people who use drugs (Beletsky et al, 2007). The criminal justice system is another venue where drug users at high risk for opioid overdose could be targeted for OEND interventions, in light of calls for the criminal justice system to align with public health goals (Silverman et al, 2012) and increased attention to the role that law enforcement officers can play in responding to the epidemic of opioid overdose death (Banta-Green et al, 2013; Davis et al, 2014; Green et al, 2013b; Ray et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…According to one study, 30% of methamphetamine users were forcibly sent to a centre by local authorities, with the median stay 90 days [11]. The 2010 Village/Commune Safety Policy, focused on “cleaning” Cambodia's streets, resulted in increased harassment, detention or arrest [12]. Following its introduction in 2011, drug-related arrests quadrupled and prison populations grew approximately 14% annually, with national prisons reaching 179% over capacity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Widespread consensus exists among government, UN agencies, NGOs and health and social service providers that in order to halt national HIV epidemics an enabling environment must be created to support HIV prevention and treatment while also ensuring law enforcement and public safety [12,18]. Therefore, to prevent further spread of HIV in Cambodia, as is the aim of the National Centre for HIV/AIDS, Dermatology and STD Control [7], it is critical to create an enabling environment in which key populations are able to access HIV and drug-related prevention, care and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a British study showed that the overall harm score for user and society for recreational cannabis (score: 20) is less than that for amphetamines (score: 23), tobacco (score: 26), cocaine (score: 27), methamphetamines (score: 33), crack cocaine (score: 54), heroin (score: 55), and alcohol (score: 72) 92 . Because medical cannabis generally tends to have a higher ratio of cbd to thc, it would be expected to be associated with a lower predilection to diversion, less addiction potential, and lower overall harm scores than those for recreational cannabis 93 .…”
Section: Cannabinoid Therapies As a Harm Reduction Strategymentioning
confidence: 99%